The Effectiveness of Neurofeedback Training on Enhancing Discrete Skills of Athletes: A Review Study - Jamil Mansouri; Reza Rostami; Ahmad Shahvaroughi; Sadegh Ranjbar (University of Tehran, 2020)
Many techniques have been invented to enhance sport performance which nowadays are used by athletes in different sport fields. Among these techniques, neurofeedback as a noninvasive brain method has received much attention. The present study was conducted to report research results of athletes' discrete skills by convenience sampling method. English articles were searched by keywords like "neurofeedback", "EEG neurofedback", "sport performance", "athletic performance", "shooting performance", "archery", "putting performance" and "golf" to collect data. The articles were collected from PsycINFO, PubMed, web of science, EBSCO and Google Scholar databases from 1990 to 2018. Persian articles were searched with same keywords in SID, Noormags, Magiran and Irandoc databases from 2001 to 2020. 16 articles had the inclusion criteria of the research and were selected. Then, the information of each article was extracted and reported in findings by an author using a specific checklist. Results showed that different recruited neurofeedback protocols in any study could affect the results of interventions and it is necessary to pay attention to this method in athletes. Based on these findings, neurofeedback training has positive effectiveness on enhancing sport performance in athletes.